LINGUISTIC CATEGORY AND GRAMMATICAL ERRORS ON SMA STUDENTS’ SPEAKING PERFORMANCE - Sahan, Anselmus; Bria, Yasintus; Ulu, Emanuel; Syahdan, Syahdan; Kariadi, Mustasyfa Thabib; Prasetyanti, Dian Chandra (English Study Program, Faculty of Teacher Training and Educational Sciences, Universitas Timor, 2023)
This study attempts to analyze the students’ speaking mastery on linguistic and grammatical elements, types of difficulty and level of errors frequently made in the school year of 2021/2022. It applied qualitative method, took 20 students as its samples and applied speaking test as its instrument which required them to speak one by one in front of the class during 3-5 minutes. Their performance was recorded by mobile phones. To analyze the data, it applied the taxonomy of linguistic category and surface strategy taxonomy. The results showed that they made 252 errors in speaking. The errors distributed on linguistic taxonomy and surface strategy taxonomy of errors. In verb, the made 48 (19%) errors; In pronoun, they made 36 (14%) errors; In preposition, they made 42 (17%) errors; In article, they made 29 (11%) errors; In singular/plural, they made 24 (10%) errors; In conjunction, they made 29 (11%) errors; In word order, they made 20 (8%) errors; and in negation, they made 24 (10%) errors. The most frequent errors are verb (48 or 19%) on linguistic strategy taxonomy while the highest frequency of the categories of grammatical errors or surface strategy taxonomy is omission (103 or 41%). It indicates that grammatical errors or surface strategy taxonomy got more errors than linguistic strategy taxonomy. The results imply that the pedagogical instruction should direct the students on speaking oral performance.